Evaluation of Islamic Education Curriculum Policy in Indonesia - Choirul Mahfud (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2019)
The most sensitive thing in the context of Islamic education policy in Indonesia is the change of curriculum. The Islamic education curriculum cannot be separated from the national education curriculum, because Islamic education is a national education subsystem. If the national education curriculum changes, then the Islamic education curriculum also changes. In this context, as adagium "changing ministers, changing curriculum" applies always interesting to discuss. This article intends to discuss how to evaluate Islamic education curriculum policies in Indonesia; and what are the supporting and inhibiting factors in implementing curriculum policies in learning in schools in Indonesia.